PELAKSANAAN PENDEKATAN DISIPLIN KERJA PADA KARYAWAN KITCHEN ALPHA HOTEL PEKANBARU - Agus Setia Ningsih; Teguh Widodo (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Alpha Hotel under the management of PT. Satu Enam Delapan Bersama that is scattered in a very strategic area in Pekanbaru, namely on Jalan Haji Imam Munandar No. 17, which is about 10 to 15 minutes from the Sultan Syarif Kasim II International Airport, Pekanbaru. Alpha Hotel was established on February 27, 2012 and is recorded in AKTA number 45, validated at the SUTRISNO ARSJAD, SH notary office. This hotel is a branch of Alpha Inn Hotel located in Medan, North Sumatra. Alpha Hotel Pekanbaru began operating as of December 14, 2013. The importance of implementing a work discipline approach to employees of the kitcheen Alpha Hotel Pekanbaru. Work discipline is the work ability of a person who is regularly, persistenly diligent and works in accordance with predetermined rules. This study uses qualitative methods, the implementation discussed in the case is modern discipline, traditional disciplionary approaches, and displinary approaches with objectives and factors that influence employees in obeying the rules and applying discipline in working at Alpha Hotel Pekanbaru. While the data collection techniques in this study used in- depth interview and documentation. Who became the key informants in this study were kitchen employees. Based on the result of research conducted, the overall results of the interviews said that kitchen employees work discipline was still increasing. Keywords : Implementation, Approach, Work discipline, Kitchen.